Effectiveness of Law Enforcement of National And International Instruments for the Protection of Traditional Cultural Expressions as Intangible Cultural Heritage in Indonesia - Suratno, Ujang; Faujura, Rahmanisa Purnamasari (Journal of Ecohumanism, 2024)
The uniqueness, preservation, protection, moral and economic rights of communities and countries of origin are important issues that require joint protection, including in Indonesia. The main focus of this study is how the legal norms of various instruments are effectively enforced against violations of the use of Traditional Cultural Expressions that contain moral rights as an identity, as well as economic rights for the survival of the owner community. This study is descriptive with an empirical legal approach, focus of the study lies in secondary data consisting of various primary and tertiery legal materials. Secondary and primary data were obtained through interviews and then analyzed empirically and legally. The study results indicate that the protection of Traditional Cultural Expressions in Indonesia as Intangible Cultural Heritage has been attempted through the integration and harmonization of international instruments into national instruments. In international level, there is the Convention for the Safeguarding of the Intangible Cultural Heritageand the Convention on the Protection of the Diversity of Cultural Expression which have been ratified into national law. The results encourage the strengthening of national instruments with special regulations on Traditional Cultural Expressions in Law No. 28 of 2014 concerning Copyright, and Government Regulation No. 56 of 2023 concerning Communal Intellectual Property Rights. However, law enforcement against instruments regulating Traditional Cultural Expressions as Intangible Cultural Heritage still has weaknesses in the substance of the regulations, limited law enforcement officers, lack of supporting facilities, and challenges to community culture, implementation is not yet effective.